Political Awareness, National Identity, and Knowledge of General Elections among Generation Z in Indonesia - Sari, Liliyana; Armalita, Rani; Rahayuningsih, Tri; Azizah, Lania Nur; Nabihah, Qurrotu Aini; Akbar, Fijay (Analitika: Jurnal Magister Psikologi UMA, 2024)
Generation Z, as the productive age group, has a significant role in the political development of a country. Although this age group is often seen as abstaining or disconnected from politics, their political awareness is essential as the nation's successors. Therefore, the present study investigated the relationship between political awareness, national identity, and knowledge about the general election among Generation Z in Indonesia. A total of 626 participants aged 17 and 21 years were recruited from 25 provinces in Indonesia using a voluntary sampling technique. Data were collected using the Political Awareness Scale and National Identity Scale, distributed through online questionnaires. The correlation analysis showed that national identity and knowledge about elections had a significant and positive relationship with political awareness with moderate strength. Moreover, the study found that most Generation Z had a high political awareness, national identity, and knowledge of the 2024 general elections. A significant difference was also reported in political awareness and national identity between Generation Z, who participated in social organizations and engaged as political party sympathizers, and those who did not. Therefore, promoting a sense of belonging to the country could foster political awareness in Generation Z, which will boost their active political participation.